1933
DOI: 10.1007/bf01342591
|View full text |Cite
|
Sign up to set email alerts
|

Zur Theorie des Diamagnetismus von Leitungselektronen

Abstract: Es wird untersucht, warm sieh in der Quantenstatistik die freie Energie otme Kenntnis der stationiiren Zust~nde des Systems bereetmen ]~lSt. 2r den hierbei entwickelten Methoden wird die diamagnetische Suszeptibilit~t "con freien Elektronen, ihre Beeinflussung dureh die ZusammenstSBe und alas magnetisehe Verhalten gebundener Elektronen untersueht. Es wird festges~ellt, bis zu welchen Feldst~rken die Suszeptibiliti~t feldunabhiingig ist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
889
0
2

Year Published

1935
1935
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,364 publications
(897 citation statements)
references
References 0 publications
6
889
0
2
Order By: Relevance
“…(Hereafter we take the unit of = k B = 1.) When we apply this approximation to the orbital susceptibility, we obtain the Landau-Peierls formula: 3,53,93) …”
Section: Diamagnetismmentioning
confidence: 99%
“…(Hereafter we take the unit of = k B = 1.) When we apply this approximation to the orbital susceptibility, we obtain the Landau-Peierls formula: 3,53,93) …”
Section: Diamagnetismmentioning
confidence: 99%
“…The model emerged from the pioneering hypothesis 5 of physicist Rudolf Peierls, who in 1933 suggested that the magnetic field induces a change in the phase of a particle -a property only indirectly detectable in quantum systems -as it travels through the lattice.…”
Section: I N D S Ay J L E B L a N Cmentioning
confidence: 99%
“…Compared with healthy individuals, people who have an impaired type I interferon response can be prone to infections, whereas individuals who have an overactive response might have autoimmune disease or organ damage associated with inflammation 3,4 . Abnormal activation of the type I interferon response is observed in most people with lupus, and a clinical study 5 found that interferon-related gene expression correlates with specific disease features.…”
Section: S a R A H M C G L A S S O N And Dav I D H U N Tmentioning
confidence: 99%
“…Harper's paper mentioned previously, there are several other early classic papers on listed in the references. [8] In 1976, R. Hofstadter's performed a numerical analysis of the problem and pointed out the beautiful self-similar structure of the energy spectrum.…”
Section: Connection To Harper's Equationmentioning
confidence: 99%